Gaung Dance as a Form of Merangin Community Cultural Identity - Nelly Indrayani; Ari Hermawan (Proceeding International Conference on Malay Identity, 2020)
Echo dance is a Merangin folk dance that reflects the culture and daily life of the people of Merangin Regency. This study aims to describe the cultural identity of the people of Merangin Regency through the background of the creation of echo dance. This research method uses qualitative research in a phenomenological approach where data is obtained through observation through watching traditional events that the author has done before the Covid-19 pandemic, as well as conducting modest interviews, and the author uses literature review in compiling this article. The results show that echo dance describes the cultural identity of the people of Merangin Regency, especially through the background of the creation of echo dance. In every movement of the echo dance, it shows a picture of the identity of the women's lives in Merangin Regency. This can be seen through the characteristics of the echo dance movement which depicts strong, strong and independent women. Keywords: echo dance, identity, culture